1985
DOI: 10.1177/0734242x8500300103
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Soil Applied Organic Compounds From Three Petroleum Wastes

Abstract: The degradation rates of three industrial wastes were evaluated under simulated land treatment conditions. A wood-preserving bottom sediment, storm-water runoff impoundment sludge, and combined API-separator/slop-oil emulsion solid waste were applied to greenhouse boxes containing Norwood silt loam or Bastrop clay soils. Soil samples were collected before waste application and 0, 180, 360 and 540 days following application. Solvent extractable organic compounds were determined gravimetrically, and a GC/MS/DS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Given the requisite environmental conditions, microbial communities are able to readily degrade these chemicals (Morgan and Watkinson 1989;Mueller et al 1989). Consequently, application of microorganisms for the remediation of contaminated soils has gained considerable interest in recent years (Bewley et al 1989;Brown et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Given the requisite environmental conditions, microbial communities are able to readily degrade these chemicals (Morgan and Watkinson 1989;Mueller et al 1989). Consequently, application of microorganisms for the remediation of contaminated soils has gained considerable interest in recent years (Bewley et al 1989;Brown et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…In both laboratory (McGinnis et al 1988;Aprill et al 1990) and field soil treatability studies (Brown et al 1985a), the majority of hazardous constituents present in creosote/pentachlorophenol (PCP) bottom sediment sludges have been rendered less toxic after undergoing degradation or transformation. However, the present investigators, utilizing the Ames test to monitor potential detoxification of creosote/PCP sludge constituents during field land treatment studies, observed a persistent mutagenic residue remaining in surface soil a year or more after the sludge was applied (Donnelly et al 1987; Barbee et al 1992).…”
mentioning
confidence: 99%